3
$\begingroup$

I must to compute value $$ [[D_{\mu}, D_{\nu}],D_{\lambda}]A^{\rho}. $$ It is equal to $$ [D_{\mu}, D_{\nu}]D_{\lambda}A^{\rho} - D_{\lambda} ([D_{\mu}, D_{\nu}]])A^{\rho} - [D_{\mu}, D_{\nu}]D_{\lambda}A^{\rho} = -D_{\lambda} ([D_{\mu}, D_{\nu}])A^{\rho}. $$ So, the question: can I formally take $A^{\rho}$ under the sign of the derivative for using the identity $[D_{\mu}, D_{\nu}]A^{\rho} = R^{\rho}_{\quad \sigma \mu \nu}A^{\sigma}$ and, afer that, take $A^{\sigma}$ outside the derivative? I'm afraid that no, but I hope that it is possible.

$\endgroup$
1
$\begingroup$

$[[D_{\mu}, D_{\nu}],D_{\lambda}]A^{\rho} = [D_{\mu}, D_{\nu}]D_{\lambda}A^{\rho}-D_{\lambda}[D_{\mu}, D_{\nu}]A^{\rho}$

$=-R^{\tau}_{{\lambda}\mu \nu}D_{\tau}A^{\rho}+R^{\rho}_{\sigma \mu \nu}D_{\lambda}A^{\sigma}- D_{\lambda}(R^{\rho}_{\sigma \mu \nu}A^{\sigma})$

$=-R^{\tau}_{{\lambda}\mu \nu}D_{\tau}A^{\rho}+ R^{\rho}_{\sigma \mu \nu ; \lambda}A^{\sigma}$

When you cycle over $\mu, \nu, \lambda$ you will need/get the first and second bianchi identities

1st BI: $R^{\tau}_{ \mu \nu \lambda}+ R^{\tau}_{\lambda \mu \nu }+ R^{\tau}_{\nu \lambda \mu } = 0$

2nd BI: $R^{\rho}_{\sigma \mu \nu ; \lambda}+R^{\rho}_{\sigma \lambda \mu ; \nu}+R^{\rho}_{\sigma \nu \lambda ; \mu}=0$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.